2016
DOI: 10.1007/s11010-016-2677-2
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic postconditioning confers cardioprotection and prevents reduction of Trx-1 in young mice, but not in middle-aged and old mice

Abstract: Thioredoxin-1 (Trx-1) is part of an antioxidant system that maintains the cell redox homeostasis but their role on ischemic postconditioning (PostC) is unknown. The aim of this work was to determine whether Trx-1 participates in the cardioprotective mechanism of PostC in young, middle-aged, and old mice. Male FVB young (Y: 3 month-old), middle-aged (MA: 12 month-old), and old (O: 20 month-old) mice were used. Langendorff-perfused hearts were subjected to 30 min of ischemia and 120 min of reperfusion (I/R group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 42 publications
9
20
0
Order By: Relevance
“…Our findings evidenced an increase in the infarct size only in old mice (20 month old), but we did not observe changes in the infarct size in middle-aged mice (12 month old). In this study we also demonstrated that PostC protocol did not confer protection in the middle-aged (12 month old) and in the old mice (>18 month old) [68]. These data are according with our finding that showed that Trx-1 levels in normoxic conditions, decreased in middle-age and old mice, compared with young mice (Fig.…”
Section: Thioredoxin In Aging Heartssupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings evidenced an increase in the infarct size only in old mice (20 month old), but we did not observe changes in the infarct size in middle-aged mice (12 month old). In this study we also demonstrated that PostC protocol did not confer protection in the middle-aged (12 month old) and in the old mice (>18 month old) [68]. These data are according with our finding that showed that Trx-1 levels in normoxic conditions, decreased in middle-age and old mice, compared with young mice (Fig.…”
Section: Thioredoxin In Aging Heartssupporting
confidence: 91%
“…At least to our knowledge, we were the first to suggest a role for Trx-1 in PostC [68]. In isolated and perfused mice heart, we demonstrated that PostC decreases the infarct size in young mice, as we expected, and this cardioprotection was abolished in middle-aged and old mice.…”
Section: Ischemic Postconditioningsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, in young mice, ischemic postconditioning conferred a protective phenotype after I/R by preventing Trx1 degradation and, thus, increasing Akt and GSK-3β phosphorylation. However, the postconditioning effect was abolished in middle-aged and older mice, as Trx1 was degraded rapidly [64, 65]. This suggests that Trx1 plays an important role in mediating the cardioprotection afforded by ischemic postconditioning.…”
Section: Role Of Trx1 In the Heart In Vivomentioning
confidence: 99%
“…On the contrary, aging suppressed the conditioning protection due to insulin insensitiveness and overexpression of PHLPP-1(a specific negative regulator of Akt) during myocardial IRI, which subsequently limited Akt activity in the aged heart (27). In addition, a new study reported that ischemic postconditioning (IPostC) failed to exert its cardioprotective effect owing to thioredoxin-1 degradation, a part of antioxidant system, and subsequently inactivated the Akt and GSK3β in middle-aged and old animals (28). In addition to the impact of the Akt pathway, the aging also affects the ERK1/2 state in the situation of IRI.…”
Section: Agingmentioning
confidence: 99%